Effects of Task Complexity, Management System and Infrastructure Support On Knowledge Sharing and Performance Enhancement - Phang, Michelle Mee Seong (2008)
The acceleration of technological change and trade liberalization in the 1990s have significantly intensified market competition and transformed the world economic infrastructure from a resource- and manufacturing-based economy to one in which knowledge and services are the key drivers of economic growth. In order for an organization to capitalize on its knowledge and truly become a learning organization, it must systematically manage and leverage knowledge existing internally and externally to create and sustain its competitive advantage. Numerous empirical studies on knowledge management have examined the relative effectiveness of various enablers, such as organizational structure, technology, culture, managerial system and strategy for knowledge creation and sharing in organizations. While these studies play a critical role in helping us to appreciate the importance of organizational enablers in knowledge management, they have neglected to examine the possible effects of task complexity and management control system (MCS) on the nature and efficacy of knowledge sharing. Similarly, the role of motivation in the domain of knowledge sharing has been overlooked. This study investigates how task complexity, MCS design and infrastructure influence the mode and effectiveness of knowledge sharing in the accounting profession and the moderating role of an individual's intrinsic motivation on the knowledge sharing process. One thousand (1,000) copIes of structured questionnaires were mailed to the Malaysian Institute of Accountants (MIA)'s members in the Klang Valley in December 2005. Of the 1,000 copies distributed, 120 completed questionnaires were returned to the researcher. After the initial stages of data analysis, follow-up interviews were carried out to obtain further insights to explain the empirical results. This study reveals that task complexity contributes significantly to knowledge sharing. It also highlights that it is not feasible to limit the professional accountants' duties to repetitive or clearly-defined procedural tasks only. Most of the tasks carried out by professional accountants are unstructured tasks which required professional judgment for task performance. While professional accountants are keen to tap into a knowledge-based system in their quest to seek possible solutions to the tasks performed, they generally hesitate to transform their tacit knowledge into a more comprehensible explicit form. The finding suggests that there may be culture-related factors which inhibit the diffusion of tacit knowledge totally and completely. The results also confirm that there is a relationship between MCS and knowledge sharing. However, different styles of MCS affect knowledge sharing differently. An interactive control system seems to support and facilitate knowledge sharing among professional accountants. Another finding of this study indicates that infrastructure has a positive effect on knowledge sharing. The results indicate that professional accountants are more willing to share knowledge within a supportive organizational infrastructure. This study also shows the significant relationship between knowledge sharing and professional competency. The results underscore the distinctive impact that the internalization mode of knowledge sharing has on professional competency. The finding implies that among the four modes of knowledge sharing, internalization is the most prolific mode of knowledge sharing among professional accountants. In addition, the study also finds that professional competency is strongly associated with firm performance. The results reveal that functional competency is the most important predictor of firm performance, particularly in its non-financial performance.